Plan de intervención psicopedagógica para el fortalecimieo de la práctica docente y el rendimiento académico de los estudiantes de segundo de bachillerato en la unidad educativa Eloy Alfaro. - Maridueña Garcia, Kerly Xiomara (2025)
The research was carried out at Unidad Educativa Eloy Alfaro in the city of Quevedo, with the purpose of designing a psychopedagogical intervention plan aimed at strengthening teaching practice and improving the academic performance of second-year high school students. The general objective was to develop a contextualized proposal that would stimulate teaching–learning processes through active and constructivist methodologies. The study adopted a mixed exploratory–descriptive approach, combining surveys of 10 teachers and 60 students, structured classroom observation, and documentary review of grades from the 2024–2025 and 2025–2026 school years. The results showed that the predominant teaching practice was characterized by a traditional approach, focused on lecture-based instruction and the limited use of teaching resources, which contributed to the persistence of low performance levels in subjects such as Mathematics and Language and Literature. Likewise, it was identified that students expressed a preference for more participatory strategies, such as teamwork, project-based learning, and linking content to their daily lives. Based on these findings, a psychopedagogical intervention plan with a constructivist approach was designed, structured in phases of diagnosis, planning, application, and evaluation, which included innovative strategies such as peer tutoring, the integration of technological resources, and formative assessment. The proposal was validated by expert judgment, who agreed on its clarity and relevance. It was concluded that the implementation of the plan constitutes a viable and necessary alternative to strengthen pedagogical practice and promote meaningful learning, contributing to raising academic performance and consolidating the teacher’s role as an active mediator in the educational process.